Improving Students’ English Writing Skill with Addie Model Teaching Approach - Ni Kadek Handini Putri; I Ketut Suardana; I Putu Eka Suardana; Ni Nyoman Ayu Tri Hidayanti (Jurnal Bahasa Inggris Terapan, 2026)
This manuscript aims to improve the first semester students of English Program, Bali Dwipa university in writing skills. This article hires qualitative method, Grounded Theory by developing the students’ competence in writing skill. The subject of the research was twenty first students of English Program, Bali Dwipa University. The model teaching used Analysis, Design, Development, Implementation, and Evaluation (ADDIE). The students are guided to establish paragraphs by developing the main topic in deductive, inductive, and both deductive and inductive strategies. The result of this research revealed that: In the analysis phase, the lecturer must have good competence to solve problems owned by the students. In the implementation phase, the students needed more times to improve their metacognition. The evaluation indicated that the students had very limited conjunctions used in the paragraphs. ADDIE is an appropriate model in teaching skill since the model enables the students to correct the error. The result of this research has significances for applied linguistic researches such as; Teaching and Learning, Semantics, Psycholinguistics, and Discourse Analysis. Therefore, the result of this research adds applied linguistics references which can be used as reference for the following research.